Loan Words from Turkish into Kurdish - Rozhan Noori Abdullah; Firas Tahsin Sabir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study entitled "Loan words from Turkish into Kurdish” is an attempt to clarify and reveal a number of words which are in Kurdish and whose origin goes back to Turkish. The researchers try to answer these research questions. How and in which way has the Kurdish language benefited from those words, have the words been taken as they are, or have they been changed in terms of their phonemes, morphemes and meaning? What are the reasons that made Kurdish language loan Turkish words and use them in its dictionary? Based on the fact that the Kurdish and Turkish languages are not from the same group and family and there is no relationship between them, but some other reasons such as neighborhood, political, economic, social, scientific, etc., resulted in the interaction between those two languages and have loaned words from one another, that the researchers are willing to shed light only on those words that have been placed into Kurdish language from Turkish. The researchers have tried to clarify their foundations and explain their morphology, to learn more about our dictionary so as to distinguish pure Kurdish words from those of borrowed in other dialects of the world. The recent study composes of an introduction, three parts, conclusions and the list of references. The first part is allocated to the definition, the concept of language, characteristics of language, Indo-European languages and the family of the Indo-Iranian Languages. In the second part, the definition of words, methods of taking words and reasons for borrowing words has been presented. The third part deals with the practical side of taking the Turkish words from Kurdish language have been revealed. At first, a brief history has presented to Turkmen in Iraq, then; the reasons behind borrowing words from Turkish into Kurdish, and finally the results and the list of sources have presented.